2018
DOI: 10.1016/s2214-109x(17)30391-1
|View full text |Cite
|
Sign up to set email alerts
|

The gendered effects of foreign investment and prolonged state ownership on mortality in Hungary: an indirect demographic, retrospective cohort study

Abstract: The European Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
4
22
0
Order By: Relevance
“…This echoes workers’ experiences in deindustrialised towns in the West, where research has found a similar long-lasting degradation (Strangleman, 2018). The results are also in accordance with the research that has shown that the expansion of the private sector has led to a rise in income inequality (Bandelj and Mahutga, 2010; Mahutga and Jorgenson, 2016) as well as mortality inequality (Scheiring et al, 2018).…”
Section: Concluding Discussionsupporting
confidence: 91%
“…This echoes workers’ experiences in deindustrialised towns in the West, where research has found a similar long-lasting degradation (Strangleman, 2018). The results are also in accordance with the research that has shown that the expansion of the private sector has led to a rise in income inequality (Bandelj and Mahutga, 2010; Mahutga and Jorgenson, 2016) as well as mortality inequality (Scheiring et al, 2018).…”
Section: Concluding Discussionsupporting
confidence: 91%
“… 31 Similarly, rapid privatization programmes in post-communist countries (linked to SDG 9, industry, renovation and infrastructure) have shaped gendered differences in mortality over and above the micro-level determinants of health. 32 SDG 8 (for promoting economic growth, full and productive employment and decent work for all) is strongly linked to health and gender. 33 , 34 Examples of interactions among SDGs 3 and 5 and other SDGs are provided in Table 1 .…”
Section: Social Determinantsmentioning
confidence: 99%
“…However, using multilevel data on settlements and individuals we have confirmed that privatisation was associated with higher mortality among men in Russia (Azarova et al . ), and among women in Hungary (Scheiring et al ., ).…”
Section: Discussionmentioning
confidence: 97%